Effect of suspended particles on thermosolutal convection of Rivlin-Ericksen fluid in porous medium with variable gravity - Aggarwal, Amrish; Dixit, Dhruva (Zielona Góra: Uniwersytet Zielonogórski)
The thermosolutal stability of a layer of the Rivlin-Ericksen fluid in a porous medium is considered under varying gravity conditions. It is found that for stationary convection, medium permeability and suspended particles have a destabilizing/stabilizing effect when gravity increases/decreases. The stable solute gradient has a stabilizing effect on the system.
Keywords: thermosolutal convection; Rivlin-Ericksen fluid; suspended particles; porous medium; varying gravity